The Effect of Oxytocin Massage on Uterine Involution in Postpartum Women in The Work Area of The Technical Implementation Unit of The Sei Pancur Community Health Center, Batam City 2023 - Nalini Julikas; Anisya Selvia; Desi Pramitha Sari (Borneo Scientific Publishing, 2024)
One of the complications of mother partum is the involution process that does not go well, called sub-involution which will cause bleeding and maternal death. One of the efforts that can be used is oxytocin massage. Oxytocin massage is done to stimulate the oxytocin reflex, stimulate uterine contractions, and accelerate uterine involution. This study aims to analyze the effect of oxytocin massage on uterine involution in postpartum mothers in the work area of the Technical Implementation Unit of the Sei Pancur Community Health Center in 2023. This type of research uses Pre-Experimental with One Group Pretest Posttest Design. The research sample amounted to 15 mothers, using an accidental sampling technique. The independent variable is oxytocin massage and the dependent variable is uterine involution. The instruments in this study were operational standards and observation sheets. The results of this study showed that uterine involution before giving oxytocin massage all experienced abnormal uterine involution 15 (100%), after giving oxytocin massage obtained normal involution 11 (73.3%) and abnormal 4 (26.6%). The Wilcoxon statistical test shows that the significant value of p-value = 0.001 < α (0.05) so there is a conclusion that there is an effect of oxytocin massage on uterine involution in postpartum mothers in the work area of the Technical Implementation Unit of the Sei Pancur Community Health Center, Batam City Year 2023.